Reform of deformation control technology for railway tunnels with squeezing surrounding rock: case study of the new and existing Wushaoling tunnels in China - Huang, Changfu; Li, Shaohua; Li, Guoliang; Yao, Tiejun; Wu, Xiaohua (Frontiers in Earth Science, 2024)
Tunnel construction subject to surrounding rock squeezing deformation can induce support cracking, intrusion, and collapse. Herein, the existing Wushaoling tunnel of Lanzhou–Wuwei second line railway and the new Wushaoling tunnel of Lanzhou–Zhangye third and fourth line railways are compared to analyze and discuss the progress in deformation control techniques for railway tunnels surrounded by squeezing rock. Further, a technical system for large deformation control is preliminarily established. The maximum support deformation of the Wushaoling tunnel do not exceed the reserved deformation. The large deformation of tunnel surrounding rock is generally controlled to achieve better support effect. The main control measures are as follows. (1) The section design method based on the deformation classification is suitable for squeezing surrounding rock. (2) The support structure design involves anti-releasing and early controlled releasing, and measures such as increased support stiffness, increased reserved deformation, and multi-layer supports can be employed. (3) The micro-bench method reduces the closure time of the inverted arch to control deformation. (4) To realize quick excavation and support and reduce the disturbance to the surrounding rock, a cantilever excavating machine can be used for excavation and an intelligent arch trolley can be utilized to realize unmanned vertical arch drilling, anchoring, and grouting.